Simulation and validation of disbond growth in co-cured composite skin–stringer specimens using cohesive elements. (March 2018) - Masood, S Nadeem; Viswamurthy, SR; Singh, Arun Kumar; Muthukumar, M; Gaddikeri, Kotresh M
Separation of skin and stringer is likely to be a failure mode in co-cured composites stiffened panels where there is considerable out-of-plane deformation. Such deformations are possible when a stiffened skin structure is loaded in compression/shear beyond buckling or in structures which contain a disbond/delamination at the skin–stringer interface. Prediction of damage initiation and progressive growth in numerical simulations require parameters such as interface fracture toughness which have to be obtained through specimen tests. Since interface toughness is generally mode dependent, this study deals with the design and testing of three different configuration of blade stiffened co-cured composite skin–stringer specimens under mode-I and mode-II dominated loading. Finite element numerical models are developed using three-dimensional cohesive elements to predict the disbond growth under mode-I and mode-II dominated loading. The work also addresses the complexities in the convergence of numerical simulations that arise due to cohesive elements. A systematic way to obtain the best values for cohesive element parameters while finding a balance between accuracy of the results, computation time and numerical stability is presented. The present cohesive element modelling and analysis methodology successfully predicted the disbond growth in skin–stringer specimen and can be used to predict disbond/delamination onset or growth in composite stiffened structures subjected to high bending.